Antibacterial activity of Moringa leaf extracts against Gram-negative bacteria from Wadi Ad-Dawasir, Saudi Arabia - Wizrah, Maha S. I.; Aldwsari, Nourah D.; Yahia, Zeinab A. (Frontiers in Microbiology, 2026)
BackgroundMoringa oleifera and Moringa peregrina have been extensively studied for their medicinal properties, particularly due to their rich content of bioactive phytocompounds. While their antibacterial effects on Gram-positive bacteria are well documented, there is a paucity of comparative studies on their efficacy against Gram-negative multidrug-resistant (MDR) strains found in arid regions.MethodsLeaf extracts of M. oleifera and M. peregrina, collected from Wadi Ad-Dawasir in Saudi Arabia, were prepared using ethanol, hot aqueous, and cold aqueous extraction methods. Their antibacterial properties were tested against Escherichia coli, Pseudomonas aeruginosa, Shigella sonnei, and Shigella shiga using the agar well diffusion method, minimum inhibitory concentration (MIC) assays (50–200 μg/mL), and scanning electron microscopy (SEM). Phytochemical analysis was conducted using gas chromatography–mass spectrometry (GC–MS) and standard qualitative methods. Amoxicillin–clavulanic acid and tetracycline were used as reference antibiotics.ResultsAll extracts showed antibacterial activity, with ethanol extracts producing the largest inhibition zones. M. peregrina was particularly effective, especially against Sh. sonnei, with an inhibition zone of 24.66 ± 0.17 mm, which surpassed that of amoxicillin–clavulanic acid (18.25 ± 1.69 mm). The MIC values were generally 50 μg/mL for both species, except for the cold extract of M. oleifera against P. aeruginosa, which had an MIC of 100 μg/mL. GC–MS analysis identified 31 compounds in M. peregrina, with stigmasterol and β-sitosterol being the most abundant. In contrast, M. oleifera was characterized by a profile rich in fatty acids. The SEM analysis revealed membrane damage in Sh. sonnei treated with the extracts, which included surface collapse, perforation, and cytoplasmic leakage.ConclusionBoth Moringa species demonstrated significant antibacterial activity against clinically important Gram-negative strains, with M. peregrina occasionally outperforming standard antibiotics. The presence of sterols in the phytochemical profile likely enhances their bactericidal action by targeting bacterial membranes. These results suggest that Moringa could serve as a viable phytotherapeutic option for addressing the growing challenge of Gram-negative bacterial resistance.